Ginsenoside Rg3 Alleviates Cisplatin Resistance of Gastric Cancer Cells Through Inhibiting SOX2 and the PI3K/Akt/mTOR Signaling Axis by Up-Regulating miR-429 - Wang, Xiaofeng; He, Rui; Geng, Li; Yuan, Jing; Fan, Huijie (Frontiers in Genetics, 2022)
Platinum-based cytotoxic chemotherapy is considered the standard treatment for advanced gastric cancer (GC). However, cisplatin chemoresistance often occurs with the mechanisms being not well clarified, which results in the cancer recurrence and poor survival. Ginsenoside Rg3, isolated from the Chinese Herb Panax Ginseng, is recognized as an anti-cancer agent. Herein, we aimed to reveal whether Ginsenoside Rg3 alleviates cisplatin resistance and sensitizes GC cells to cisplatin-induced apoptosis, and draw out the underlying molecular mechanism in cisplatin-resistant GC cells. The lower expression of miR-429 was found in AGSR-CDDP cells; it was also in association with cisplatin-resistance in GC cells and expression of which was restored following Ginsenoside Rg3 treatment. We also demonstrated that miR-429 made a contribution toward chemosensitivity in GC cells partly through SOX2 regulation. SOX2 was found to contribute to developing platinum resistance and was an authentic target for miR-429 in AGSR-CDDP cells. Importantly, enforced expression of SOX2 with a pcDNA3-SOX2 construct lacking the 3′-UTR miRNA binding site diminished the cytotoxic effects of miR-429 in AGSR-CDDP cells. We demonstrated that Ginsenoside Rg3 enhanced chemosensitivity in AGSR-CDDP GC cells, at least in part, through up-regulating miR-429, thereby targeting SOX2 and modulating downstream PI3K/AKT/mTOR signaling. Ginsenoside Rg3 was also found to regulate apoptosis-related genes via miR-429 in cisplatin-resistant GC cells. Ginsenoside Rg3 treatment significantly suppressed the migration rate of AGSR-CDDP GC cells, while following transfection with anti-miR-429, the anti-migratory effects of Ginsenoside Rg3 was partially abolished. This data suggested that Ginsenoside Rg3 may impede the chemoresistance and migration of GC cells mainly mediated through miR-429. We concluded that miR-429-regulated SOX2 expression was one of the main mechanisms by which Ginsenoside Rg3 dramatically promoted its anticancer effects on cisplatin-resistant GC cells. We also underscored a supporting model in which miR-429 adjusted PI3K/AKT/mTOR signaling by regulating SOX2 in cisplatin-resistant GC cells.